Diseño de estrategia para el mejoramiento del clima organizacional en la ebsagro madre tierra ONG en el municipio de Samacá, Boyacá. - Rodríguez Salcedo, Sergio Esteban (Universidad Antonio Nariño, 2022)
This research, as a general objective, proposed to design a strategy that will improve the organizational climate of the ebsagro Madre Tierra ONG in the municipality of Samacá, Boyacá, through three specific objectives, the first to identify the factors that need to be analyzed to improve the performance of the activities of ebsagro, the second to implement variables between the factors of the organizational system and the needs of the workers, and the third to provide tools to the area of human talent to facilitate the process of improving the organizational climate.